Pengaruh Dosis Sekam terhadap Pertumbuhan dan Hasil Tanaman Padi (Oryza sativa L.) Varietas Inpari 32 - Tita Kartika Dewi; Lusiana Lusiana; Hamdan Drian Adiwijaya; Buki Hermawan; Nine Wahyuni Maulani (Lembaga Penelitian dan Pengabdian Universitas Winaya Mukti, 2023)
The research aims to determine; (1) the response of growth and yield of rice plants to various doses of roasted husks, and (2) doses of roasted husks that have a positive effect on the growth and yield of rice plants of the Inpari 32 variety. The study was carried out for 3 (months) months, starting from January to March 2022. This research was carried out with an experimental approach using a Randomized Block Design (RBD), 6 doses of burnt husk treatment and repeated five times, so that there were 30 experimental units. The variables observed were plant height, number of tillers per clump, number of productive tillers per clump, number of shoots per clump, panicle length, number of pithy grain per panicle, weight of 1000 grains of grain, yield of dry grain harvested per clump and per plot. The data obtained in the study were analyzed by analysis of variance (ANOVA) if there was a significant effect, then Duncan's multiple-distance further test was carried out at a significance level of 5 percent. The results showed: (1) Burned husk treatment had a significant effect on plant height, number of tillers per clump, number of productive tillers per clump, number of panicles per clump, number of pithy grain per panicle, weight of 1000 grains of grain, yield of dry grain harvested per clump. and per plot, but had no significant effect on panicle length. and (2) The highest harvested dry grain yields were obtained at doses of roasted husks of 4 and 5 tons/ha, namely 6.65 kg and 7.70 kg per plot or equivalent to 7.39 tonnes per hectare and 8.56 tonnes per hectare.